2019
DOI: 10.1186/s40249-019-0543-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the nonhuman primate reservoir of Schistosoma mansoni in Africa: a systematic review

Abstract: Background: Reports of natural infections of Schistosoma mansoni in a number of species of nonhuman primates (NHPs) in Africa, coupled with the substantial overlap of NHP habitats and human schistosomiasis endemic areas, has led to concerns about the role of NHPs in the transmission of human schistosomiasis. We conducted a systematic review of the literature to describe the current scope of knowledge for Africa, for the NHP species implicated, their geographical distribution, infection rates with S. mansoni, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“… 8 By contrast, in sub-Saharan Africa, Schistosoma mansoni , the main cause of intestinal schistosomiasis in humans, is reported to occur only occasionally in non-human primates and rodents. 9 , 10 , 11 , 12 Furthermore, Schistosoma haematobium is believed to be capable of naturally infecting humans only (and very rarely non-human primates 10 ), and was traditionally considered to be the sole cause of human urogenital schistosomiasis. In this context, current control programmes in sub-Saharan Africa, which are based on preventive chemotherapy or mass administration of the anthelmintic praziquantel, target only humans (primarily school-aged children) and ignore the potential role of zoonotic reservoirs and the obstacle that they might pose to achievement of control and elimination goals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 By contrast, in sub-Saharan Africa, Schistosoma mansoni , the main cause of intestinal schistosomiasis in humans, is reported to occur only occasionally in non-human primates and rodents. 9 , 10 , 11 , 12 Furthermore, Schistosoma haematobium is believed to be capable of naturally infecting humans only (and very rarely non-human primates 10 ), and was traditionally considered to be the sole cause of human urogenital schistosomiasis. In this context, current control programmes in sub-Saharan Africa, which are based on preventive chemotherapy or mass administration of the anthelmintic praziquantel, target only humans (primarily school-aged children) and ignore the potential role of zoonotic reservoirs and the obstacle that they might pose to achievement of control and elimination goals.…”
Section: Introductionmentioning
confidence: 99%
“…8 By contrast, in sub-Saharan Africa, Schistosoma mansoni, the main cause of intestinal schistosomiasis in humans, is reported to occur only occasionally in non-human primates and rodents. [9][10][11][12] Furthermore, Schistosoma haematobium is believed to be capable of naturally infecting humans only (…”
Section: Introductionmentioning
confidence: 99%
“…Cercariae then move to the lungs and liver through blood, and develop to the stage of schistosomula, schistosome worms, that continually produce eggs which are shed to the environment through human excreta. These eggs, once in a freshwater environment, hatch out to miracidia, to infect specific snails to complete the lifecycle [ 18 , 19 ]. It has long been recognized that environmental factors, such as temperature, precipitation, elevation, soil, and vegetation may limit or promote the distribution of schistosomiasis transmission [ 20 , 21 ], although some mechanistic understandings of these impacts are largely confined to S. japonicum in China and the Philippine [ 17 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies conducted in the 1960s and 1970s comprehensively demonstrated that several NHP were able to maintain transmission of schistosomiasis and maintain the parasitic cycle [8][9][10]. Several field surveys have demonstrated that NHP can naturally host S. mansoni [11]. Natural S. mansoni infections have been evidenced in grivet monkeys (Chlorocebus aethiops) in Ethiopia [12][13][14][15], Kenya [16,17] and Tanzania [14], in patas monkeys (Erythrocebus patas) in Cameroon [18], in chimpanzees (Pan troglodytes) in Nigeria [19] and Senegal [20], and in baboons (Papio sp.)…”
Section: Introductionmentioning
confidence: 99%